Astragaloside IV attenuates ferroptosis after subarachnoid hemorrhage via Nrf2/HO-1 signaling pathway - Liu, Zhuanghua; Zhou, Zhaopeng; Ai, Pu; Zhang, Chunlei; Chen, Junhui; Wang, Yuhai (Frontiers in Pharmacology, 2022)
Subarachnoid hemorrhage (SAH) is a severe type of stroke featuring exceptionally high rate of morbidity and mortality due to the lack of effective management. Ferroptosis can be defined as a novel iron-dependent programmed cell death in contrast to classical apoptosis and necrosis. Astragaloside IV (AS-IV) is an active ingredient extracted from Astragalus membranaceus with established therapeutic effect on CNS diseases. However, the exact role of ferroptosis in Astragaloside IV-mediated neuroprotection after SAH is yet to be demonstrated. In the present study, the SAH model of SD male rats with endovascular perforation was used to gauge the neuroprotective effect of AS-IV on SAH-induced early brain injury (EBI) and to clarify the potential molecular mechanism. We found that the induction of SAH reduced the levels of SLC7A11 and glutathione peroxidase 4 (GPX4) in the brain, exacerbated iron accumulation, enhanced lipid reactive oxygen species (ROS) level, and stimulated neuronal ferroptosis. However, the administration of AS-IV and the ferroptosis inhibitor Ferrostatin-1 (Fer-1) enhanced the antioxidant capacity after SAH and suppressed the accumulation of lipid peroxides. Meanwhile, AS-IV triggered Nrf2/HO-1 signaling pathway and alleviated ferroptosis due to the induction of SAH. The Nrf2 inhibitor ML385 blocked the beneficial effects of neuroprotection. These results consistently suggest that ferroptosis is profoundly implicated in facilitating EBI in SAH, and that AS-IV thwarts the process of ferroptosis in SAH by activating Nrf2/HO-1 pathway.